Extreme magnification of an individual star at redshift 1.5 by a galaxy-cluster lens. (April 2018) - Kelly, Patrick; Diego, Jose; Rodney, Steven; Kaiser, Nick; Broadhurst, Tom; Zitrin, Adi; Treu, Tommaso; Pérez-González, Pablo; Morishita, Takahiro; Jauzac, Mathilde; Selsing, Jonatan; Oguri, Masamune; et al.
Abstract Galaxy-cluster gravitational lenses can magnify background galaxies by a total factor of up to ~50. Here we report an image of an individual star at redshiftz  = 1.49 (dubbed MACS J1149 Lensed Star 1) magnified by more than ×2, 000. A separate image, detected briefly 0.26″ from Lensed Star 1, is probably a counterimage of the first star demagnified for multiple years by an object of ≳3 solar masses in the cluster. For reasonable assumptions about the lensing system, microlensing fluctuations in the stars' light curves can yield evidence about the mass function of intracluster stars and compact objects, including binary fractions and specific stellar evolution and supernova models. Dark-matter subhaloes or massive compact objects may help to account for the two images' long-term brightness ratio. An individual star atz  = 1.49 is gravitationally lensed and highly magnified by a foreground galaxy cluster. Fluctuations in the star's emission provide insight on the mass function of intracluster stars, compact objects and the presence of dark-matter subhaloes.